Zoonotic pathogen screening of striped field mice (Apodemus agrarius) from Austria. Issue 2 (21st February 2021) - Jeske, Kathrin; Herzig‐Straschil, Barbara; Răileanu, Cristian; Kunec, Dusan; Tauchmann, Oliver; Emirhar, Duygu; Schmidt, Sabrina; Trimpert, Jakob; Silaghi, Cornelia; Heckel, Gerald; Ulrich, Rainer G.; Drewes, Stephan
Abstract: The striped field mouse ( Apodemus agrarius ) is known to carry several zoonotic pathogens, including Leptospira spp. and Dobrava–Belgrade orthohantavirus (DOBV). Since its first detection in 1996 in south‐east Austria, the striped field mouse has further expanded its range in Austria. Here, we screened 35 striped field mice collected in an Austrian region near the Hungarian border for DOBV, Leptospira spp. and seven vector‐borne pathogens. Hantavirus RT‐PCR screening and DOBV IgG ELISA analysis led to the detection of two DOBV‐positive striped field mice. The complete coding sequences of all three genome segments of both strains were determined by a combination of target enrichment and next‐generation sequencing. Both complete coding S segment sequences clustered within the DOBV genotype Kurkino clade with the highest similarity to a sequence from Hungary. In one of 35 striped field mice, Leptospira borgpetersenii sequence type (ST) 146 was detected. Bartonella spp., Borrelia miyamotoi and Neoehrlichia mikurensis DNA was detected in four, one and two of 32 mice, respectively. Babesia, Anaplasma, Ehrlichia and Rickettsia specific DNA was not detected. Future investigations will have to determine the prevalence and invasion of these pathogens with the ongoing range expansion of the striped field mouse in Austria.